Growth, Distribution, and Poverty in Africa : Messages from the 1990s - Christiaensen, Luc (Washington, DC: World Bank, 2013)
This book synthesizes, and elaborates on the results of a series of country studies, completed under the Poverty Dynamics in Africa Initiative, organized by the Africa Region of the Bank. These studies made use of vastly improved household survey data, which have enhanced understanding of African poverty dynamics during the past decade. The book examines the main factors behind observed poverty changes in eight countries - Ethiopia, Ghana, Madagascar, Mauritania, Nigeria, Uganda, Zambia, and Zimbabwe. After reviewing the trends in income poverty and other, more direct measures of well-being (such as education, health, and nutrition), the authors go beyond the aggregate numbers, and highlight the insights to be gained from unraveling the microeconomic data. These data reveal systematic distributional effects, linking growth and poverty, which lead to some groups' gaining from episodes of economic growth, and others being left behind. It further describes those groups left behind, and calls for public action to ensure that all poor Africans gain from future economic growth.